Sosialisasi Pencegahan dan Penanganan Kekerasan Seksual di SMP Islam Kebumen Kec. Sumberjo, Kab.Tanggamus - Yonnawati Yonnawati; M. Johan Candradinata; Saidah Saidah; Nirani Sundawati Atib; Rizkika Ramadhani; Jasendra AHD; Siti Soviah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Sexual violence in the school environment is a serious issue that requires special attention. This Real Work Lecture (KKN) activity aims to provide understanding and skills to students, teachers and education staff at Kebumen Islamic Middle School in preventing and handling sexual violence. Through outreach and training programs, it is hoped that a school environment that is safe and free from sexual violence will be created. The results of this activity show increased awareness and skills in handling sexual violence situations.